Evolution of the structural and phase states of a Ti-6Al-4V alloy in forming submicrocrystalline structure with the use of temporary hydrogenation; Russian Physics Journal; Vol. 49, N 4 - Grabovetskaya G. P.; Melnikova E. N.; Kolobov Yu. R.; Chernov I. P. Ivan Petrovich; Naidenkin E. V.; Nikitenkov N. N.; Mishin I. P. (2006, 2006)
В фонде НТБ ТПУ отсутствует